Lusoblothrus, a new syarinid pseudoscorpion genus (Arachnida) from Portugal, occupying an isolated position within the Holarctic fauna - Reboleira, Ana Sofia P. S.; Zaragoza, Juan A.; Gonçalves, Fernando; Oromí, Pedro (Zootaxa, 2012)
The new pseudoscorpion genus Lusoblothrus of the family Syarinidae is described from a cave in the Algarve region, southernPortugal, to accommodate L. aenigmaticus sp. nov., whose morphological affinities within the Holarctic syarinid fauna are notclear and resembles the Gondwanan genera. This discovery emphasizes the relevance of the Algarve region as a hotspot for relictual hypogean fauna within the Iberian Peninsula.